College Student Internet Use: Convenience and Amusement - Genevieve M. Johnson (The Canadian Network for Innovation in Education (CNIE), 2007)
Four hundred five college students completed a questionnaire that assessed patterns of Internet use. Results describe college students, with rare exception, as Internet users. The vast majority of college students frequently communicate online and access websites. While an Internet game experience is typical, relatively few college students are heavy online gamers. Overwhelmingly (i.e., 77.8%), college students conceptualized the Internet as a convenience, although 17.8% considered the Internet a source of amusement. Approximately 5% of college students reported negative perceptions of the Internet (frustrating or a waste of time). Principal component analysis revealed three patterns of online behaviour; integrated-Internet-use, games-only use, and dating-only use. Implications for online instructional practice are presented. Résumé : Quatre cent cinq étudiants du niveau collégial ont répondu à un questionnaire mesurant leurs tendances de l'utilisation d'Internet. Les résultats présentent ces étudiants comme des usagers d'Internet, à quelques exceptions près. La grande majorité de ces étudiants utilisent fréquemment les outils de communication en ligne et naviguent sur Internet. Alors qu'une expérience de jeu en ligne s'avère commune, peu d'étudiants du collège s'avèrent être des joueurs en ligne excessifs. Essentiellement (c.à-d. 77,8 %), ces étudiants perçoivent Internet comme une commodité, même si 17,8 % d'entre eux le considère comme une source d'amusement. Environ 5 % ont indiqué des perceptions négatives d'Internet (frustrations ou pertes de temps). L'analyse en composantes principales a révélé 3 tendances de comportements en ligne, l'utilisation intégrée d'Internet, l'utilisation seule de jeux et l'utilisation à des fins de rencontre seulement. On présente des conséquences pour la pratique de l'enseignement en ligne.